The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12903-022-02322-y
|View full text |Cite|
|
Sign up to set email alerts
|

Gingival shape analysis using surface curvature estimation of the intraoral scans

Abstract: Background Despite many advances in dentistry, no objective and quantitative method is available to evaluate gingival shape. The surface curvature of the optical scans represents an unexploited possibility. The present study aimed to test surface curvature estimation of intraoral scans for objective evaluation of gingival shape. Methods The method consists of four main steps, i.e., optical scanning, surface curvature estimation, region of interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Root morphology affects root volume of the tooth so evaluating root morphology could also be beneficial in future studies [30]. In future studies, it could be valuable to analyze the gingival shape of the alveolar cleft with intraoral scans [31]. Intraoral scans were not available for all the patients in our study; however, this could be an interesting future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Root morphology affects root volume of the tooth so evaluating root morphology could also be beneficial in future studies [30]. In future studies, it could be valuable to analyze the gingival shape of the alveolar cleft with intraoral scans [31]. Intraoral scans were not available for all the patients in our study; however, this could be an interesting future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that digital assessment using CBCT imaging was effective and noninvasive to characterize the phenotypic features of the periodontium compared with clinical methods and histologic assessments [ 22 26 ]. In comparison to CBCT, intraoral scanning yield greater precision in capturing soft tissue morphotypes, encompassing aspects such as crown and GM, the curve of the gingival margin, and papilla height (PH) [ 27 , 28 ]. Research has suggested that integrating CBCT images with intraoral scanning data could comprehensively assess the periodontal phenotype of both bone and soft tissue in clinical practice [ 21 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%